A study of the factors associated with delays in diagnosis and treatment of tuberculosis among pulmonary tuberculosis patients in Sunsari district. - Choudhari, Manish (2011)
ABSTRACT: This cross sectional study was conducted with the objective to identify the factors associated with the patients delay in first consultation with the health care provider and providers delay in diagnosis of tuberculosis among pulmonary TB patents attending DOTS centers in Sunsari District. A total of 215 cases were enrolled in the study. Out of study population, 42.4% were in age group 15-34 years and 31.6% in age group more than 50 years. The median age of the respondents was 36 years. About 65.6% were male and 34.4% female. Many (29.8%) of them were from Tharu and Tarai middle castes. Most (68.4%) of them were married and 25.1% unmarried. One third (32.1%) of the respondents were illiterate. An equal percentage of the respondents were from rural (50.7%) and urban (49.3%) area. Unemployed (21.9%) and housewives (21.4%) were major occupational categories. This study revealed that patient delays consist of 76.6% of the total delay. The median patient delay, health care provider delay and treatment delay were 42 days, 10 days and 0 days respectively. The median total delay was 56 days with range of 8 to 378 days. in this study, about 67.4% of the patients consulted health care provider only after 30 days of recognizing symptoms. Sixty percent of the patients were delayed more than one week for the diagnosis of TB by the health care providers The reasons for the patient delay for the first consultation in this study were domestic preoccupation (65.5%), lack of knowledge about TB (43.4%), poor socioeconomic condition (18.3%). About 52.6% of the patients consulted government health facility for the first time of consultation followed by private clinic (29%), drug store (14.4%), and traditional healer (4.7%). Only about 22.8% have correct knowledge about the exact cause of TB. Majority of the respondents cited cough for more than two weeks (61.9%), fever (41.9%), haemoptysis (37.2%) and chest pain (30.7%) as the symptoms of TB. Most (74.9%) of the respondents cited sputum microscopy as a method of diagnosis of TB. More than half (52.6%) answered that there is no any side effects of anti TB drug.